Differences in Posttraumatic Stress Disorder, Depression, and Attribution of Symptoms in Service Members With Combat Versus Noncombat Mild Traumatic Brain Injury. Issue 1 (January 2020) - Hardy, Morgan; Kennedy, Jan; Reid, Matthew; Cooper, Douglas
Abstract : Objective: This study compares combat-related mild traumatic brain injury (mTBI) to non-combat-related mTBI in rates of posttraumatic stress disorder (PTSD) and depression after injury, severity of postconcussive symptoms (PCSs), and attribution of those symptoms to mTBI versus PTSD. Participants: A total of 371 active duty service members (SMs) with documented history of mTBI, divided into combat and non-combat-related cohorts. Design: Retrospective cohort study. Main Measures: Diagnoses of PTSD and depression based on medical record review and self-report. PCSs measured using Neurobehavioral Symptom Index. Attribution of symptoms based on a rating scale asking how much mTBI, PTSD, depression, deployment, or readjustment stress contributed to current symptoms. Results: Prevalence of PTSD was significantly higher after a combat-related mTBI, compared with a noncombat mTBI ( P = .001). Prevalence of depression did not differ between the 2 groups. PCSs were high in both combat and noncombat mTBIs, with no statistical difference between groups. SMs with PTSD reported higher PCS, regardless of combat status. SMs without PTSD attributed symptoms mainly to mTBI, whereas SMs with PTSD, regardless of combat status, were much more likely to attribute symptoms to PTSD, depression, and deployment/readjustment stress. Conclusions: This research contributes to our understanding of the complex interplay between mTBI and PTSD in both combat and noncombat injuries within the military population and the importance of addressing both simultaneously.